Radical treatment for walled‐off necrosis: Transmural nasocyst continuous irrigation. Issue 3 (29th January 2019) - Tamura, Takashi; Itonaga, Masahiro; Tanioka, Kensuke; Kawaji, Yuki; Nuta, Junya; Hatamaru, Keiichi; Yamashita, Yasunobu; Yoshida, Takeichi; Ida, Yoshiyuki; Maekita, Takao; Iguchi, Mikitaka; Kitano, Masayuki
Abstract : Background and Aim: Treatment efficiency of walled‐off necrosis (WON) using endoscopic ultrasound‐guided drainage (EUS‐D) with a double pigtail stent (DPS) is limited. Endoscopic necrosectomy is often carried out if EUS‐D fails. However, endoscopic necrosectomy is associated with significant morbidity and mortality. Thus, we developed transmural nasocyst continuous irrigation (TNCCI) as an alternative therapeutic option for WON. This study aimed to evaluate the usefulness of TNCCI therapy for WON. Methods: Between April 2009 and March 2018, 19 of 39 patients admitted with WON underwent EUS‐D. Ten consecutive patients also received TNCCI therapy (TNCCI group) between May 2015 and March 2018. TNCCI was carried out by inserting an external tube from the gastroduodenal lumen into the WON under endoscopic ultrasonography guidance and then continuously irrigating the WON with saline at a rate of 40 ml/h. Nine consecutive patients who underwent EUS‐D without TNCCI therapy between April 2009 and April 2015 were used for comparison (control group). Various parameters were compared between the TNCCI and control groups. Results: Time taken to reduce WON (6 vs 32 days, P = 0.001), implementation rate of endoscopic necrosectomy (0% vs 55.6%, P = 0.01), and number of endoscopic necrosectomy sessions per patient (0 vs 0.8 ± 1.0, P = 0.008) were significantly lower in the TNCCI group than in the control group. Conclusions: Walled‐off necrosis can be effectively and safely treated by endoscopic drainage with a DPS and TNCCI. This technique can be an alternative therapeutic option before carrying out endoscopic necrosectomy.